Hybrid CRITIC–VIKOR method for objective-based component selection in ICT infrastructure planning for university laboratory systems - Pratiwi, Merina; Syarief, Amiroel Oemara (Institute of Computer Science (IOCS), 2025)
Selecting appropriate hardware materials is a critical aspect in planning computer laboratory infrastructure at higher education institutions, aiming to support effective technology-based learning. This study aims to evaluate and identify the optimal hardware material alternatives by applying an integrated CRITIC–VIKOR approach to multi-criteria decision making (MCDM). The CRITIC method is employed to determine objective weights for each criterion based on standard deviation and inter-criteria correlation, while the VIKOR method is used to rank the alternatives through a compromise solution approach. Nine hardware material alternatives including types of casings, cooling systems, and cables were assessed against five key criteria: cost, durability, energy efficiency, compatibility, and availability. The analysis results show that Energy Efficiency had the highest objective weight (0,260563785), followed by Durability (0,234238828) and Availability (0,211419693). Based on the compromise index (Q), the best alternatives in each category were Steel Casing (Q = 0,059737547), Liquid Cooler (Q = 0,350101862), and Braided Cable (Q = 0.0000). These findings demonstrate that the integrated CRITIC–VIKOR method effectively produces objective and balanced evaluations. This model may serve as a strategic decision-making tool for higher education institutions in the procurement of computer laboratory hardware based on data-driven considerations.